Medical Students’ Perception on Joining Military Medical Services: A Mixed Method Study - Shrestha, Bipin Kumar; Shrestha, Rashmi (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Currently, in Nepal there are 19 Medical Colleges, most of them under Tribhuwan University and Kathmandu University. Nepalese Army Institute of Health Sciences (NAIHS) is Not-for-profit organization run by Nepal Army Welfare Fund, affiliated to Tribhuwan University. Excluding the medical graduates from abroad there are around 1500 doctors graduating from Nepal every year. After graduation they have the options joining as a Medical Officer in hospitals around Nepal or go abroad. Joining the Military Medical services seems appealing. However the options are broadening with the jobs in the private and other sectors becoming more lucrative. This study attempts to explore the perception of medical students on joining the Military Medical services. Methods: The study was conducted during November 2016 to December 2017 among first and second year MBBS students of NAIHS. Comprehensive information about becoming a Military doctor in Nepal Army Medical Corps was provided. Student perceptions about joining Military Medical Services were studied using the semi-structured questionnaire. Informed written consent was taken from the students for the study. Results: From the total (204) respondents, 64.7% (132) chose to join the Military medical services. Among the responses, serving the nation, job security and opportunity for career development were the most chosen. Reponses like; preferring private practice, less pay/salary, and deployment consideration were the reasons for not choosing to join the Military Medical Services. Conclusion: Job as a Military Doctor seems attractive to majority of the Medical students. Male and Female medical students are equally interested towards becoming a military doctor in Nepal Army.